The effect of accounting conservatism on investing in selected companies - Taherinia, Masoud; Arjomandi, Zeinab Khalil (Opción, 2019)
The purpose of the study is to investigate the effect of accounting conservatism on investment in companies selected by the Tehran Stock Exchange during the global financial crisis by combined data method. The results of the model estimation showed that accounting conservatism did not have a significant effect on investment in selected companies of the Tehran Stock Exchange during the global financial crisis. In conclusion, conservative companies during the global financial crisis tend to be less inferior to investing